The Impact of Peer-mediated Intervention on Children with Special Needs in Inclusion Classroom - Muqoddam, Faqihul; Hendriani, Wiwin (TAZKIYA Journal of Psychology, 2020)
Systematic review aims to analyze the impact of interventions that mediated by peers on children with special needs in an inclusion setting. The review was conducted with the search keywords "peers" and "inclusive class", "peers" and "inclusion settings", "peers" and "inclusive settings", "peers" and "inclusive classrooms" in 2 online databases, namely ERIC and ScienceDirect. There were 11 articles reviewed from the total number of initial searches of 1,233 obtained from screening results according to inclusion and exclusion criteria. The results show that all interventions that have been implemented involve the role of peers. The focus of interventions various kinds, ranging from children aged 3-16 years and more focus on children with Autism Spectrum Disorder (ASD). Eleven Interventions that involve peers are significantly able to improve interaction, communication, social skills and social initiation in children with special needs so that it can be a reference in the process of intervention in the further application or research.